Use of Nanoparticles in Pharmaceutical and Drug Delivery Systems: Advances and Challenges - Ibrahim, Awais; Sehar ul Islam; Razaq, Rabeea; Siddique, Sana; Rao, Muhammad Azeem; Sardar, Nimra; Gardazi, Syed Mohsin Ali; Sabir, Anum; Bashir, Malka Saba; Rehana (Indus Journal of Bioscience Research, 2025)
Nanoparticles represent a significant innovation in pharmaceutical drug delivery, tackling essential issues such as inadequate solubility, restricted bioavailability, and systemic toxicity of medicinal medicines. Their distinctive physicochemical characteristics, such as nanoscale dimensions, elevated surface area-to-volume ratio, and adjustable surface functions, provide accurate targeting and regulated drug release, rendering them essential for contemporary medicine. This review synthesizes contemporary advances, obstacles, and emerging trends in nanoparticle-mediated drug delivery methods. This analysis focuses on essential nanoparticle types, including liposomes, polymeric nanoparticles, and lipid nanoparticles, emphasizing their applications in oncology, gene therapy, and RNA-based vaccinations. Despite significant advancements, the analysis highlights persistent limitations such as biocompatibility, stability, regulatory obstacles, and deficiencies in comprehending biodistribution and long-term toxicity. The paper examines creative strategies to tackle these issues, including stimuli-responsive nanoparticles, theranostic systems, and biomimetic designs. Moreover, it underscores the use of cutting-edge innovations, such as artificial intelligence for nanoparticle optimization and advanced manufacturing methods, to improve scalability and efficiency. Future research will be enhanced by resolving the current shortcomings and broadening the applicability of nanoparticles to fields such as regenerative medicine and brain-targeted therapeutics. This study highlights the revolutionary capacity of nanoparticles to improve pharmaceutical drug delivery and emphasizes the necessity for ongoing interdisciplinary collaboration to convert these advancements into clinical and economic success.